On the Structural Transformation of Rural Africa - Barrett, Christopher B.; Christiaensen, Luc; Sheahan, Megan; Shimeles, Abebe (World Bank, Washington, DC, 2017)
From 2000 to 2014, per capita gross domestic product in Sub-Saharan Africa increased by almost 35 percent in real terms, doubling in some countries. Such progress happened while agricultural productivity growth remained low in the aggregate, despite some bright spots, and poverty reduction was steady but discouragingly slow. This paper argues that ending extreme poverty will require structural change in agriculture, and in rural African economies more broadly. Drawing on a range of recent research, the paper outlines broad priority areas for policy actions to accelerate productivity and initiate structural change in the agriculture sector and the rural nonfarm economy.